Interim Evaluation of the Tier 1 Program (Secondary 1 Curriculum) of the Project P.A.T.H.S.: First Year of the Full Implementation Phase - Daniel T. L. Shek; Hing Keung Ma; Rachel C. F. Sun (The Scientific World Journal)
To understand the implementation quality of the Tier 1 Program (Secondary 1 Curriculum) of the Project P.A.T.H.S. (Positive Adolescent Training through Holistic Social Programmes) in the full implementation phase, 100 schools were randomly selected to participate in personal and/or telephone interviews regarding the quality of the implementation process of the Tier 1 Program. In the interviews, the participants described the responses of the students to the program, the perceived benefits of the program, the perceived good aspects of the program, and the areas requiring improvement, difficulties encountered in the implementation process, and perceived attributes of the worker-support scheme (“Co-Walker Scheme”). Results showed that most workers perceived that the students had positive responses to the program and the program was beneficial to the students. They also identified several good aspects in the program, although negative comments on the program design and difficulties in the implementation process were also recorded. Roughly half of the respondents had positive comments on the “Co-Walker Scheme”. In sum, the respondents generally regarded the program as beneficial to the students and they were satisfied with the Tier 1 Program (Secondary 1 Curriculum) in the full implementation phase, although some implementation difficulties were also expressed.